Identification of inducible clindamycin resistance in Staphylococcus areus methicillin resistance from clinical isolates by d-zone test - Sareh Saadat; Kavous Solhjoo; Akbar Kazemi; Jalal Mardaneh (فصلنامه دانشگاه علوم پزشکی جهرم, 2013)
Introduction: The increasing incidence of infections caused by strains of Staphylococcus aureus, especially methicillin-resistant (MRSA), has led to the increased use of effective antibiotics such as clindamycin and erythromycin for treatment of systemic and local infections caused by this organism. However, concern over the possibility of emergence of clindamycin resistance during therapy has discouraged some clinicians from prescribing it. The aim of this study was to identify the induced clindamycin resistance in clinical isolates of methicillin-resistant Staphylococcus aureus. Materials and Methods: In this cross-sectional study, 100 S.aureus strains isolated from clinical specimens were collected from laboratories in Shiraz (Shahid Faghihi, Nemazi and MRI) hospitals. Re-identification of the isolates was performed by conventional microbiological and biochemical testes. Methicillin resistant strains were selected by disc diffusion method, and inducible clindamycin resistance in these strains was identified using D-zone Test. Results: The result of susceptibility testing showed that out of 100 Staphylococcus aureus samples 44 isolates (44%) were resistant to methicillin. Forty-six percent of the isolates were resistant to erythromycin and 51% to clindamycin. Conclusion: The results showed that performing D-zone test in clinical laboratories for identification of induced clindamycin resistance, reporting the results to the physician for prescribing these two antibiotics for treatment of infections caused by inducible clindamycin resistant strains, and replacing the appropriate treatment regimen are essential measures to be taken.